A semantic description language for RESTful data services to combat semaphobia - Lanthaler, Markus; Guetl, Christian (IEEE Computer Society, 2011)
RESTful Web services are an increasingly popular way for companies to expose their data on the Web. On the other hand, the Linked Open Data initiative is gaining traction re-cently. Since REST’s principles align well with those of Linked Data, there is an increasing interest in the relationship of the two. Nevertheless, in practice they still largely remain separated, creating islands of data instead of a global graph of data forming the envisioned Semantic Web. There are different reasons for this. One is the reluctance of most Web developers to use Semantic Web technologies, a phenomenon we denote as Semaphobia. Another reason is that the Semantic Web is consi-dered to be a disruptive technology which does not consider exist-ing infrastructure. This makes it difficult for enterprises to update their legacy systems. To solve these and other issues, we propose a novel approach to semantically describe RESTful Data Services which in consequence leads to a mechanism to transform the data provided by such services to semantic resources. This aims to contribute to the availability of more semantic datasets. By keeping the approach as familiar and simple as possible for Web developers, we hope to lower the entry barrier and to foster the adoption of our approach.